Fishing parameters of the vessels of various types in the Azov and Black Sea Basin in 2017–2021 - Stafikopulo, A.M.; Vtyurina, N.V.; Gorbatyuk, Ya.I. (Водные биоресурсы и среда обитания, 2022)
This article considers the key aspects of the industrial fisheries in the Azov and Black Sea Basin over the last five years. The factors, determining its parameters and performance, have been analyzed; they include technical specifications and operational characteristics of the vessels of various types engaged in fishing activity, time expenditures for fishing operations, catches per unit effort, fishing areas, the state of fish stocks, the number of vessels in operation, and other characteristics. Daily vessel activity reports on the main fishing targets—European anchovy, European sprat, Black Sea sprat, gobies — for 2017–2021 have been processed; comparative data on the performance of the vessels of various types, as well as the trends in industrial fishing parameters, are presented for the investigated period. A comparative analysis of the vessels engaged in industrial fishing in the Azov and Black Sea Basin and belonging to four types — medium fishing freezer trawler, small-size fishing trawler, receiving and transporting refrigerator, refrigerating fishing seiner-trawler — has been conducted. The most high-performance types of vessels for the target species have been identified. It is also noted that, in recent years, fishing seiners and refrigerating fishing seiner-trawlers started to be involved into the fishing of other commercial species: veined rapa whelk, Black Sea turbot, and horse mackerel (fishing with light attractor). The data presented will make it possible to assess the present status of the industrial fisheries. В статье рассмотрены основные аспекты судового промысла в Азово-Черноморском бассейне за последние пять лет. Проанализированы факторы, определяющие параметры и показатели судового промысла: технические и производственные характеристики судов различных типов, участвующих в промысле, временные затраты на ведение промысла, уловы на усилие, районы лова, состояние сырьевой базы объектов лова, количество судов, выходящих на промысел, и другие. Обработаны судовые суточные донесения о ...